Desain dan penerimaan pengguna portal posyandu “juara” Surakarta berbasis google site - Choironnisa, Pumaya Vintarnauri Tria; Suswardany, Dwi Linna; Utami, Riyani Wahyu (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Integrated health service post recording and reporting is a crucial step in improving the efficiency and quality of public health services. Purpose: To analyze the design and user acceptance of the Surakarta “juara” integrated health service portal based on google site. Method: Research and Development with user acceptance evaluation using an online questionnaire with a Likert scale of 1–4. Results: The mean scores for perceived usefulness (3.53), perceived ease of use (3.32), and behavioral intention to use (3.43) were above the midpoint of the scale, indicating positive user acceptance. The majority of respondents found the portal useful in the reporting process and did not report major technical challenges, although a small number of respondents reported issues related to digital literacy, interface design, and the need for feature development. Conclusion: This study indicates that the portal is perceived as useful and relatively easy to use, and has potential for continued use. However, further development and user support are needed for more inclusive and optimal use. Suggestion: Further research is recommended to test the relationship between technology acceptance variables using the TAM or UTAUT model inferentially, as well as adding objective performance indicators, such as login frequency, completeness and timeliness of reporting, input completion time, and error rate. Keywords: Digital Health System; Google Sites-Based; Integrated Health Service Post Portal; User Acceptance. Pendahuluan: Digitalisasi pencatatan dan pelaporan posyandu merupakan upaya penting dalam meningkatkan efisiensi dan kualitas layanan kesehatan masyarakat. Tujuan: Untuk menganalisis desain dan penerimaan pengguna portal posyandu “juara” Surakarta berbasis google site. Metode: Research and Development dengan evaluasi penerimaan pengguna melalui kuesioner daring menggunakan skala Likert 1–4. Hasil: Nilai rata-rata perceived usefulness (3.53), perceived ease of use (3.32), dan behavioral intention to use (3.43) berada di atas titik tengah skala, yang mengindikasikan penerimaan pengguna yang positif. Mayoritas responden menilai portal membantu proses pelaporan dan tidak melaporkan kendala teknis utama, meskipun sebagian kecil responden menyampaikan adanya isu terkait literasi digital, desain antarmuka, dan kebutuhan pengembangan fitur. Simpulan: Penelitian menunjukkan bahwa portal dipersepsikan bermanfaat dan relatif mudah digunakan, serta memiliki potensi untuk digunakan secara berkelanjutan, dengan tetap memerlukan pengembangan lanjutan dan dukungan pengguna agar pemanfaatannya lebih inklusif dan optimal. Saran: Penelitian selanjutnya disarankan untuk menguji hubungan antarvariabel penerimaan teknologi menggunakan model TAM atau UTAUT secara inferensial, serta menambahkan indikator kinerja objektif, seperti frekuensi login, kelengkapan dan ketepatan waktu pelaporan, waktu penyelesaian input, dan tingkat kesalahan (error rate). Kata Kunci: Berbasis Google Site; Penerimaan Pengguna; Portal Posyandu; Sistem Kesehatan Digital.